1966
DOI: 10.1152/ajplegacy.1966.210.4.801
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic activity in smooth muscle from small subcutaneous arteries

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0
1

Year Published

1967
1967
1991
1991

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 6 publications
5
36
0
1
Order By: Relevance
“…Unlike most arterial preparations, it is a spontaneously active tissue, and in this respect, it may well resemble the smaller blood vessels (Johansson & Bohr, 1966). It also differs from arterial preparations in its sensitivity to drugs; for instance histamine, 5-hydroxytryptamine, bradykinin and angiotensin all have relatively feeble effects when compared to the catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most arterial preparations, it is a spontaneously active tissue, and in this respect, it may well resemble the smaller blood vessels (Johansson & Bohr, 1966). It also differs from arterial preparations in its sensitivity to drugs; for instance histamine, 5-hydroxytryptamine, bradykinin and angiotensin all have relatively feeble effects when compared to the catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have shown that potassium at the increased concentrations observed in venous blood during exercise and hypoxia can relax smooth muscle both in vivo (5)(6)(7)(8)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and in vitro (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Therefore, this ion.…”
mentioning
confidence: 99%
“…Because there is evidence that the magnitude of vascular response (-AR) to K+ is a function of the 1.7 (8) 139.3±1.6 (17) [Ca++], meq/liter 3.7+0.1 (22) 3.9i0.1 (8) 3.7+0.1 (18) [Mg++], meq/liter 1.8240.02 (22) 1.8540.12 (8) 1.85±0.06 (18) Hct, ml/100 ml 42.1+0.5 (74) 42.840.9 (24) 42.8+0.8 (25) 43.241.1 (25) Means±SEM; number of observations indicated in parentheses. Because there were significant correlations between IR and AR and because IR was significantly greater in hypertensives than in normotensives, we also compared responses in hypertensives and normotensives by using analysis of covariance, which adjusted responses for their regression on initial resistance.…”
Section: Resultsmentioning
confidence: 99%
“…These observations have naturally led us to speculate that there may be an underlying defect in Na+-K+-ATPase enzyme systems in vascular smooth muscle in renal hypertensives (9). Such a defect could decrease the activity of the cellular electrogenic pump, tending to depolarize cell membranes, either generally, or in specific "pacemaker" cells (25). Membrane depolarization might account for the impaired vascular relaxation and decreased stimulatory thresholds (26) in hypertension.…”
Section: Resultsmentioning
confidence: 99%